European Perceptions of Islam and America from Saladin to George W. Bush - O'Brien, P. author. aut Link
X, 230 p.
Keywords: This book considers European perceptions of their rivals throughout history from the Islamic civilization between the first Crusade in 1095 and the final Ottoman siege of Vienna in 1683 to the United States of America from independence in 1776 until the present and investigates Europe's capacity to lead the world.